Hubungan Antara Pengetahuan, Sikap, dan Perilaku Tidak Aman Dengan Kejadian Kecelakaan Kerja Pada Pekerja Ketinggian MTH 27 Office Suite Tahun 2021: The Relationship Between Knowledge, Attitude, and Unsafe Behavior and the Incidence of Work Accidents Among Height Workers at MTH 27 Office Suite - Syrly Alvera Ayunigtiyas; Hedy Herdiana; Mohamad Yaser (MPI Press, 2025)
Introduction: Work accidents are caused by unsafe human actions (unsafe acts) and unsafe conditions. These incidents may be influenced by knowledge, attitudes, and unsafe behavior of workers. Objectives: This study aimed to determine the relationship between knowledge, attitudes, and unsafe behavior with the incidence of work accidents among high-altitude workers at MTH 27 Office Suite in 2021. Method: This research used a quantitative method with a cross-sectional approach. The data used were primary, collected through questionnaires and interviews, as well as secondary data from previous studies. Data were analyzed using univariate and bivariate analysis through the Statistical Product and Service Solution (SPSS) software. Result: The study found no significant relationship between knowledge and work accidents (p = 0.054). However, there was a significant relationship between attitudes and work accidents (p = 0.037), and between unsafe behavior and work accidents (p = 0.021). Conclusion: This research concludes that attitudes and unsafe behavior are significantly related to the incidence of work accidents among high-altitude workers, while knowledge is not significantly related.